The Effect of Product Quality and Service Quality on Customer Satisfaction at SLV Room Boutique - Abd Rachman; Muhammad Ilham Wardhana Haeruddin; Muh. Ichwan Musa; Chalid Imran Musa; Tenri S.P. Dipoatmodjo (PT. Maju Malaqbi Makkarana, 2023)
The purpose of the study was to determine the effect of product quality and service quality on customer satisfaction at the SLV Room Boutique. The population in this study were consumers of SLV Room Boutique. the sampling in this study was carried out using a purposive sampling technique so that 80 respondents were sampled. The type of research used is quantitative. The data used is primary data obtained by distributing questionnaires to consumers. The results of the study after the data was processed with SPSS.23 show that there is a partially significant effect between the independent variable and the dependent variable which can be proven by the calculated t value of the product quality variable (X1) of 2,938> t table 1.665 with a significant value of 0.004 <0.05 and the calculated t value of the service quality variable (X2) of 4.700> t table 1.665 with a significant value of 0.000 <0.05. Simultaneously there is a positive and significant effect on the dependent variable (X2). Simultaneously, there is a positive and significant influence between the independent variables on the dependent variable as evidenced by the multiple linear regression equation, namely Y = -0.754 + 0.167 X1 + 0.338 X2 + e and a significant effect with a calculated F value of 56.016 > F table 3.965 with a significant level of 0.00 <0.05. The R Square value or the coefficient of determination of 0.593 indicates that 59.3% of the customer satisfaction variable (Y) is influenced or can be explained by the independent variables of product quality and service quality, while the remaining 40.7% is explained by other variables not included in this study. Simultaneously there is a positive and significant effect on the dependent variable (X2). Simultaneously, there is a positive and significant influence between the independent variables on the dependent variable as evidenced by the multiple linear regression equation, namely Y = -0.754 + 0.167 X1 + 0.338 X2 + e and a significant effect with a calculated F value of 56.016 > F table 3.965 with a significant level of 0.00 <0.05. The R Square value or the coefficient of determination of 0.593 indicates that 59.3% of the customer satisfaction variable (Y) is influenced or can be explained by the independent variables of product quality and service quality, while the remaining 40.7% is explained by other variables not included in this study. Simultaneously there is a positive and significant effect on the dependent variable (X2). Simultaneously, there is a positive and significant influence between the independent variables on the dependent variable as evidenced by the multiple linear regression equation, namely Y = -0.754 + 0.167 X1 + 0.338 X2 + e and a significant effect with a calculated F value of 56.016 > F table 3.965 with a significant level of 0.00 <0.05. The R Square value or the coefficient of determination of 0.593 indicates that 59.3% of the customer satisfaction variable (Y) is influenced or can be explained by the independent variables of product quality and service quality, while the remaining 40.7% is explained by other variables not included in this study. there is a positive and significant influence between the independent variables on the dependent variable as evidenced by the multiple linear regression equation, namely Y = -0.754 + 0.167 X1 + 0.338 X2 + e and a significant effect with a calculated F value of 56.016> F table 3.965 with a significant level of 0.00 <0.05. The R Square value or the coefficient of determination of 0.593 indicates that 59.3% of the customer satisfaction variable (Y) is influenced or can be explained by the independent variables of product quality and service quality, while the remaining 40.7% is explained by other variables not included in this study. there is a positive and significant influence between the independent variables on the dependent variable as evidenced by the multiple linear regression equation, namely Y = -0.754 + 0.167 X1 + 0.338 X2 + e and a significant effect with a calculated F value of 56.016> F table 3.965 with a significant level of 0.00 <0.05. The R Square value or the coefficient of determination of 0.593 indicates that 59.3% of the customer satisfaction variable (Y) is influenced or can be explained by the independent variables of product quality and service quality, while the remaining 40.7% is explained by other variables not included in this study. 338 X2 + e and a significant effect with a calculated F value of 56.016> F table 3.965 with a significant level of 0.00 <0.05. The R Square value or the coefficient of determination of 0.593 indicates that 59.3% of the customer satisfaction variable (Y) is influenced or can be explained by the independent variables of product quality and service quality, while the remaining 40.7% is explained by other variables not included in this study. 338 X2 + e and a significant effect with a calculated F value of 56.016> F table 3.965 with a significant level of 0.00 <0.05. The R Square value or the coefficient of determination of 0.593 indicates that 59.3% of the customer satisfaction variable (Y) is influenced or can be explained by the independent variables of product quality and service quality, while the remaining 40.7% is explained by other variables not included in this study.